2020
DOI: 10.1038/s41591-020-1073-3
|View full text |Cite
|
Sign up to set email alerts
|

Midkine rewires the melanoma microenvironment toward a tolerogenic and immune-resistant state

Abstract: An open question in aggressive cancers such as melanoma is how malignant cells can shift the immune system to pro-tumourigenic functions. Here we identify Midkine (MDK) as a melanoma-secreted driver of an "inflamed", but immune evasive, microenvironment that defines poor patient prognosis and resistance to immune checkpoint blockade. Mechanistically, MDK was found to control the transcriptome of melanoma cells allowing for a coordinated activation of NF-B and downregulation of interferon-associated pathways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 66 publications
11
88
0
Order By: Relevance
“…Treatment with BO‐110 started when the cutaneous lesions were palpable (around 100 mm 3 ; see arrows for all panels in Fig 6 ) and proceeded for 2 weeks. In the absence of BO‐110, both of these lines are very aggressive as previously reported (Olmeda et al , 2017 ; Cerezo‐Wallis et al , 2020 ). In these conditions, Vegfr3 Luc emission correlated with tumor growth at the site of implantation (Fig 6B and J ), and was induced systemically in the lymph nodes (Fig 6C and K ), spleen (Fig 6D and L ), lung (Fig 6F and M ), and liver (Fig 6E and N ).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Treatment with BO‐110 started when the cutaneous lesions were palpable (around 100 mm 3 ; see arrows for all panels in Fig 6 ) and proceeded for 2 weeks. In the absence of BO‐110, both of these lines are very aggressive as previously reported (Olmeda et al , 2017 ; Cerezo‐Wallis et al , 2020 ). In these conditions, Vegfr3 Luc emission correlated with tumor growth at the site of implantation (Fig 6B and J ), and was induced systemically in the lymph nodes (Fig 6C and K ), spleen (Fig 6D and L ), lung (Fig 6F and M ), and liver (Fig 6E and N ).…”
Section: Resultssupporting
confidence: 81%
“…In particular, our findings revealing circulating MDK as a biomarker that reflects reduced tumor burden after BO‐110 treatment may prove useful to assess the antitumoral activity of this compound beyond less specific IFN‐associated markers. Importantly, we have recently reported that MDK exerts potent immune‐suppressive roles on macrophages and cytotoxic T cells (Cerezo‐Wallis et al , 2020 ). Therefore, pharmacological blockade of MDK may have the added value of not only interfering with tumor neolymphangiogenesis and metastasis, but also impinging on the immune milieu.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, EGLN3 inactivation attenuated interleukin 4-induced M2 polarization, as indicated by decreased mRNA and protein expression of arginase (Arg) 1 (Fig. 5N, O), a marker of M2 macrophages [37]. Albeit to a less extent, EGLN3 inactivation promoted M1 polarization of macrophages, as judged by the expression of inducible nitric oxide synthase (iNOS) (Fig.…”
Section: Genetic Inactivation Of Egln3 Hydroxylase Inhibits Macrophag...supporting
confidence: 64%
“…Serum midkine levels in healthy subjects are mostly determined within a narrow range that depends on the applied detection system. Beyond these "background" levels, several diseases are known to be accompanied by elevated midkine serum levels, e.g., cancers of different origin, ischemia of brain, limbs or kidneys [33], and congestive heart failure [4,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Midkine received its designation as a heparin binding factor, which was initially described as an embryonic growth factor with strong expression during mid-gestation and within kidneys. Pleiotropic functions have been identified beyond pregnancy, involving cellular survival programs, chemotaxis of neutrophils [1], and propagation of neoangiogenesis [2][3][4]. The potency of this specific growth factor is illustrated in experimental animal models with genetic ablation of the midkine (MDK) gene.…”
Section: Introductionmentioning
confidence: 99%